2016
DOI: 10.1016/j.physleta.2015.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency and edge breathers in the discrete sine-Gordon system via subharmonic driving: Theory, computation and experiment

Abstract: We consider a chain of torsionally-coupled, planar pendula shaken horizontally by an external sinusoidal driver. It has been known that in such a system, theoretically modeled by the discrete sineGordon equation, intrinsic localized modes, also known as discrete breathers, can exist. Recently, the existence of multifrequency breathers via subharmonic driving has been theoretically proposed and numerically illustrated by Xu et al. in Phys. Rev. E 90, 042921 (2014). In this paper, we verify this prediction exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This finding, i.e. the wider range of stabilization of the EB relative to the BB, has been also experimentally observed in a chain of coupled pendula [26].…”
Section: A Driving Near the Lowest Frequency Modesupporting
confidence: 77%
“…This finding, i.e. the wider range of stabilization of the EB relative to the BB, has been also experimentally observed in a chain of coupled pendula [26].…”
Section: A Driving Near the Lowest Frequency Modesupporting
confidence: 77%
“…In mechanical lattices, the study of nonlinear waves dates back to the classical 1D Fermi-Pasta-Ulam-Tsingou (FPUT) lattice [20], with its 2D extension still being analyzed quite recently [21,22]. Coupled pendula have been extensively studied in terms of synchronization and destabilization [23], while coherent structures therein such as breathers continue to capture considerable interest [24][25][26]. Nonlinear elastic metamaterials known as granular crystals have attracted much recent attention [27], with topological effects already demonstrated [28].…”
mentioning
confidence: 99%
“…Since then, there has been a wide variety of systems in which experimental observations of structures have been reported that are exponentially localized in space and periodic in time. Among them, one can note arrays of Josephson junctions [4,5], mechanical [6,7] and magnetic pendula [8], microcantilevers [9], electrical chains [10,11], granular crystals, [12,13], ionic crystals such as PtCl [14] and antiferromagnets [15]. Moreover, these types of structures have been offered as plausible explantions of experimental findings in settings such as the DNA denaturation [16], α-uranium [17] or NaI [18]; see also the relevant review of [19].…”
Section: Introductionmentioning
confidence: 99%